Disability, Gender and Class: Complex Interactions in Ghimire's Jeevan Kada Ki Phool (Research Journal, 2024)
This article aims at exploring the complex intersection of gender, disability, and class in Jhamak Ghimire's Jeevan Kada Ki Phool, an autobiographical work originally written in the Nepali language. Basedon the theoretical framework of intersectionality developed by black feminist Kimberly Crenshaw, the study examines how these overlapping identities contribute to a unique and intensified experience of oppression. I use free transliteration and translation while citing from the work. The analysis reveals that Ghimire's marginalization does not occur due to these factors operating in isolation, but rather the simultaneous effects of her gender, physical disability, lower economic status, and societal expectations that operate together. By examining the interconnection of these forms of oppression, the article focuses on the multifaceted challenges that Ghimire coped with, and the deep impact they had in various ways on her life. The study also reveals the resilience that she displays to combat such deep-rooted systems of marginalization.